2007
DOI: 10.1093/hmg/ddm289
|View full text |Cite
|
Sign up to set email alerts
|

A block of autophagy in lysosomal storage disorders

Abstract: Most lysosomal storage disorders (LSDs) are caused by deficiencies of lysosomal hydrolases. While LSDs were among the first inherited diseases for which the underlying biochemical defects were identified, the mechanisms from enzyme deficiency to cell death are poorly understood. Here we show that lysosomal storage impairs autophagic delivery of bulk cytosolic contents to lysosomes. By studying the mouse models of two LSDs associated with severe neurodegeneration, multiple sulfatase deficiency (MSD) and mucopol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
419
2
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 470 publications
(447 citation statements)
references
References 37 publications
23
419
2
3
Order By: Relevance
“…51 The presence of abnormal mitochondria in LSDs was initially attributed to the general defect of the autophagic pathway-ineffective lysosomalautophagosomal fusion. 13,52 However, recent studies have indicated that multiple mechanisms which occur prior to the entrapment of aberrant mitochondria into autophagosomes underlie their accumulation in these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…51 The presence of abnormal mitochondria in LSDs was initially attributed to the general defect of the autophagic pathway-ineffective lysosomalautophagosomal fusion. 13,52 However, recent studies have indicated that multiple mechanisms which occur prior to the entrapment of aberrant mitochondria into autophagosomes underlie their accumulation in these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis in mouse models of multiple sulphatase deficiency and mucopolysaccharidosis indicated that changes in cholesterol levels determine the ability of lysosomes to fuse with endocytic and autophagic vesicles 39 through the regulation of the SNARE fusion machinery. 21 Studies in Niemann Pick type C patient cells and in mouse models showed that cholesterol also influences autophagy initiation by enhancing Beclin1 levels 40 or SNARE-mediated autophagosome maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is vital for basal homeostasis and for promoting survival during cellular stress by nutrient recycling and removal of damaged proteins and organelles 8 . Importantly, lysosomal dysfunction is tightly linked to defective protein clearance via the autophagy pathway [9][10][11] .…”
mentioning
confidence: 99%
“…The clinical picture of MSD is complex and combines the symptoms of individual sulfatase deficiencies including severe neurodegeneration, skeletal abnormalities, facial dysmorphism, organomegaly and premature death 7 . Recent studies, including the generation of the Sumf1 À / À mouse, have elucidated important links between the pathogenesis of MSD and inhibition of the autophagy pathway 4,9 .…”
mentioning
confidence: 99%